FUZZY INFERENCE SYSTEM DALAM MENENTUKAN STATUS MALNUTRITION PADA BALITA DI KOTA BATAM - Simanjuntak, Pastima; Eko Suharyanto, Cosmas (STKIP PGRI Sumatera Barat, 2019)
Batam is one of the most advanced industrial cities in the western part of Indonesia. The industry in Batam City is divided into heavy industry and light industry. Heavy industry is dominated by shipyard industry, metal industry, steel industry and so on. While the light industry includes the electronics industry, garment industry, plastic industry and so on. Industrial locations in Batam City are scattered in several places that are tailored to the type and yield of the company. One of the health factors that occurred in the city of Batam, namely there are still many children who experience malnutrition. Malnutrition is a body or body that experiences malnutrition for a long time and generally occurs in children, malnutrition in children is caused by a lack of balanced nutritious food intake, besides that it can also be caused by certain diseases that cause disruption of the process digestion of food or disruption of absorption of important nutrients needed by the body. In the world of Bad Nutrition health is called Heavy Protein Energy Malnutrition (MEP), the solution to this problem is using fuzzy logic with the Sugeno method. This method uses constants or mathematical functions from input variables, and in the defuzzification process uses a centralized average method. The output value of malnutrition status is 83.85 which means it is not included in malnutrition status.